Role Of Porcine Base Anticoagulant During Prengnancy And Puerperium As Prophylaxis Treatment In Venos Thromboembolism (VTE): Syariah Views And Perspectives - Irwan Mohd Subri; Nur Zaireena Zainal; Mohd Nasir Abd Majid; Nadeeya'ayn Umaisara Mohamad Nor; Zizi Azlinda Mohd Yusof; Azman Ab Rahman (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
Indexed by Scopus